The Effect of Compensation and Work Environment on Employee Productivity through Job Satisfaction as Intervening Variable - Mifta Arif Salam; Sumardi Lasise; Musran Munizu (Hasanuddin Journal of Business Strategy, 2022)
This research aims to find out the effect of compensation and the work environment on employee productivity through job satisfaction as an intervening variable in the case of employment social security (BPJS Ketenagakerjaan) in Makassar. This research was carried out at the BPJS Ketenagakerjaan Makassar office by collecting information from permanent employees who had worked for more than 3 (three) years using questionnaires. The sampling method used is purposive sampling the study is able to obtain a sample of 25 employees. The data is analyzed with a quantitative approach and processed using SPSS application version 25. The results of this study showed that compensation, work environment, and job satisfaction had a direct positive and significant effect on employee productivity. It also found that both compensation and work environment had a positive and significant effect on job satisfaction. Job satisfaction is also found to be able to mediate compensation and work environment when relating to employee productivity.